IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA SURABAYA NOMOR 41 TAHUN 2021 DALAM PELAYANAN PERIZINAN ONLINE SURABAYA SINGLE WINDOWS (SSW) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA SURABAYA - Dwi Marelita Sari (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Public Service is a series of activities in the process of fulfilling citizens' needs for goods, services and administrative services that must be prepared by public service implementers such as state management organizations, legal entities, independent institutions formed from laws even if only for public service activities.  One part of the public service is the licensing service.  By utilizing technology, an electronic-based public service can be carried out.  One of the innovations that have been implemented by the Surabaya city government is the innovation of a technology-based licensing service system called Surabaya Single Windows (SSW). The purpose of this research is to find out how to implement Surabaya Mayor Regulation Number 41 of 2021 concerning Business Licensing, Non-Business Licensing, and Non-Licensing Services.  This research is a descriptive qualitative research.  This research focuses on the implementation of Surabaya Mayor Regulation Number 41 of 2021. In this study the primary data sources consist of employees of the Investment Service and One Stop Integrated Services and the public who use the Surabaya Single Windows Program through techniques.  Data were collected by questionnaire, observation, and interview methods.  The data analysis technique used by the researcher is descriptive narrative. Based on the results of the research, the researchers concluded that the implementation of Surabaya Mayor Regulation Number 41 of 2021 Concerning Business Licensing, Non-Business Licensing and Non-Licensing Services in the City of Surabaya has been going well, but not yet optimal.  Not optimal because the technical team is not in the same building, which slows down the processing of complaints, while the rest can be considered good.